Matrix Metalloproteinases in Cerebral Vasospasm following Aneurysmal Subarachnoid Hemorrhage. (3rd April 2013) - Mehta, Vivek; Russin, Jonathan; Spirtos, Alexandra; He, Shuhan; Adamczyk, Peter; Amar, Arun P.; Mack, William J.
Abstract : Delayed cerebral vasospasm is a significant cause of morbidity and mortality following aneurysmal subarachnoid hemorrhage (SAH). While the cellular mechanisms underlying vasospasm remain unclear, it is believed that inflammation may play a critical role in vasospasm. Matrix metalloproteinasees (MMPs) are a family of extracellular and membrane-bound proteases capable of degrading the blood-rain barrier (BBB). As such, MMP upregulation following SAH may result in a proinflammatory extravascular environment capable of inciting delayed cerebral vasospasm. This paper presents an overview of MMPs and describes existing data pertinent to delayed cerebral vasospasm.